Current State of Target Treatment in BRAF Mutated Melanoma - Tanda, Enrica Teresa; Vanni, Irene; Boutros, Andrea; Andreotti, Virginia; Bruno, William; Ghiorzo, Paola; Spagnolo, Francesco (Frontiers in Molecular Biosciences, 2020)
Incidence of melanoma has been constantly growing during the last decades. Although most of the new diagnoses are represented by thin melanomas, the number of melanoma-related deaths in 2018 was 60,712 worldwide (Global Cancer Observatory, 2019). Until 2011, no systemic therapy showed to improve survival in patients with advanced or metastatic melanoma. At that time, standard of care was chemotherapy, with very limited results. The identification of BRAF V600 mutation, and the subsequent introduction of BRAF targeting drugs, radically changed the clinical practice and dramatically improved outcomes. In this review, we will retrace the development of molecular-target drugs and the current therapeutic scenario for patients with BRAF mutated melanoma, from the introduction of BRAF inhibitors as single agents to modern clinical practice. We will also discuss the resistance mechanisms identified so far, and the future therapeutic perspectives in BRAF mutated melanoma.